Comparison of nutritional status and dietary pattern among mothers who delivered term low birth weight and normal birth weight infant at Hospital Universiti Sains Malaysia - Siew, Ooi Good (2018)
Low birth weight (LBW) is defined as infant’s birth weight less than 2500 gram regardless of gestational age. Low birth weight is a global public health problem and it is the major cause of infant’s mortality and morbidity either in neonatal or in the first year of life. LBW infants will also lead to chronic diseases in adulthood such as diabetes, hypertension and coronary heart disease. There are many risk factors associated with the delivery of LBW infants especially nutritional status of mothers is one of the important risk factors. This cross-sectional study was carried out to determine the nutritional status, dietary pattern and other associated risk factors with low birth weight (LBW) among mothers who delivered low birth weight (LBW) and normal birth weight (NBW) infants. A total of 408 mothers with 204 mothers who delivered low birth weight (LBW) and normal birth weight (NBW)(n=204) infants were recruited based on the inclusion criteria and exclusion criteria at Hospital Universiti Sains Malaysia, Kelantan, Malaysia. Data collected include sociodemographic, socioeconomic, obstetric/medical history, the maternal dietary pattern was assessed by using the Food Frequency Questionnaire (FFQ) and nutritional status was assessed by anthropometric measurements. Results showed that the incidence LBW infants during this study period was 12.1% (622 of 5152 total birth). In the descriptive analysis, there were significantly different for mothers with LBW and NBW infants by age, level of education, numbers of children, gravida, parity and number of attendance to antenatal care. In term of nutritional status, mothers with NBW infant have higher mean of BMI: 23.84(5.19) compared to mothers with LBW infants mean: 22.60(5.29) (p=0.018). Rice, drinking water, sugar, sea fish, leafy green vegetable and traditional local cake were highly consumed food items by both groups except biscuit and chicken were highly consumed by mothers who delivered NBW infants, but moderately consumed by mothers of LBW infants. There was no significant difference of total score in dietary diversity among mothers who delivered NBW and LBW infants, however, there was a significant difference in meat products and egg (p<0.005). Multiple logistic regression analysis after adjusted for the confounder, found that there factor associated significantly with low birth weight include education (ORadj 3.30; 95% C.I. 1.27, 8.60, 5.97, p=0.015), parity (ORadj 0.76; 95% C.I. 0.66, 0.87, 14.34, p=<0.001) , history of previous child birth LBW (ORadj 0.49; 95% C.I. 0.25, 0.96, 4.37, p=0.037), hypertension in previous pregnancies (ORadj 0.24; 95% C.I. 0.72, 0.81, 5.28, p=0.022) BMI (ORadj 0.95; 95% C.I. 0.92, 1.00, 4.85, p=0.028). In future research, it is recommended to evaluate dietary intake based on Malaysian Recommended Nutrient Intake of pregnant women apart from the dietary diversity score.